PEMBELAJARAN SEJARAH PADA MASA PANDEMI COVID-19 DI MAN 2 ACEH TAMIANG TAHUN 2020 - yana, Meldariska (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Kependidikan, 2022)
The purpose of this study is to describe how the implementation of history learningduring the Covid-19 pandemic and to describe the obstacles and advantages ofhistory learning during the Covid-19 pandemic. This research is a qualitativeresearch using descriptive method. Data collection techniques by observation,interviews and documentation studies. The analysis is carried out by collecting dataaccording to the actual facts and then the data is compiled, processed, and analyzedto provide an overview of the existing problems. The results of this study indicate thatthe process of learning history during the covid-19 pandemic at MAN 2 AcehTamiang was based on distance learning using internet media to make it easier toaccess learning materials. the efforts made are by using google classroom, whatsapp,google from to facilitate the learning process, by sending videos, pictures, or notburdening students with many assignments and the advantages of learning historyduring the covid-19 pandemic at MAN 2 Aceh Tamiang, namely teachers can makelesson plans, prepare learning media, facilitate communication in learning, and makelearning more relaxed. As well as barriers to learning history during the covid-19pandemic at MAN 2 Aceh Tamiang, namely students experiencing problems in quotasand signals. During the teaching and learning process, students did not listen to theexplanation of the material from the teacher and some students had to borrow aneighbor's cellphone. It is recommended for teachers to have good competence,especially in using learning methods in history subjects, in addition, history teachersare required to be more creative in the process of implementing history lessons.